REFORMASI KEBIJAKAN HUKUM PIDANA TERHADAP PELAKU PEDOFILIA DALAM PERSPEKTIF SIYĀSAH TASYRI’IYYAH - Imam Hafas; Yuli Kasmarani (Tazir, 2023)
Cases of sexual violence against children are a serious problem that can have lasting effects, both physically and psychologically. To minimize and prevent this, the government has made changes in determining penalties for perpetrators of sexual violence against children (pedophilia) to deter and fear them. This research is a library study regarding changes in criminal law policy for pedophilia perpetrators from a siyāsah tasyri'iyyah perspective using a juridical-normative method and primary and secondary sources that are descriptive-analytic in nature and analyzed using a juridical-normative approach based on state theory. law, criminal law policy, and siyāsah tasyri'iyyah. The results of the research can be concluded that the changes in criminal law that occurred in Indonesia were adapted to the social conditions of society, namely in the view of siyāsah tasyri'iyyah, in making changes to criminal law policy pedophiles have realized the values ​​of the Qur'an and Sunnah. This policy change is also a form of government responsibility in protecting human rights. Keywords: Pedophilia, Criminal Law Policy, Siyāsah Tasyri'iyyah.